Projective Experiments and Local Productive Chains of Constructive Systems with Bamboo Culms - Barata, Tomás Queiroz Ferreira; Sasaoka, Silvia [UNESP]; dos Santos, Gabriel Fernandes; Ferrari, Ariel (Springer Nature, 2023)
In recent decades, a growing appreciation of the use of renewable source materials in design and architecture arose, challenging the competence of designers in selecting inputs for the creation of artifacts and building systems with an emphasis on social and environmental sustainability. Bamboo, both as a plant and as a material, is an excellent element for nature-based technical solutions, stimulating and orienting learning toward more sustainable development. Aiming to meet local demands, this chapter’s objective is to present alternative construction techniques involving the culture and productive chain of bamboo in projects for building contemporary systems and components. Its methodology is organized according to the following procedures: (a) establishment of a theoretical framework on the use of bamboo culms in civil construction and architecture, with emphasis on the handling process, prefabrication, production, and assembly of components and constructive systems; (b) survey of documentation and graphic pieces of projects and products; (c) data survey through technical visits to construction sites; (d) data analysis and systematization of project typologies and the different steps in the production chain of constructive systems, taking into account the present context in the interior of São Paulo, Brazil. Results point to the improvement in the quality of constructive components in production processes made with bamboo culms and the optimization and qualification of the productive chain of this material on a local scale.
Keywords: Bamboo culms; Bamboo in natura; Building systems; Modular panels; Production chain; Reciprocal frame; Sustainable construction; Trusses